Does the use of a specialised paediatric retrieval service result in the loss of vital stabilisation skills among referring hospital staff?. Issue 10 (19th September 2003) - Ramnarayan, P; Britto, J; Tanna, A; Thomas, D; Alexander, S; Habibi, P
Abstract : Aims: To compare the proportion of airway and vascular access procedures performed by referring hospital staff on critically ill children in two discrete time periods, before and after widespread use of a specialised paediatric retrieval service. Methods: Transport data were obtained from retrieval logs of all children for whom a paediatric retrieval team was launched in each of two time periods (October 1993 to September 1994; and October 2000 to September 2001). Results: The overall intubation rate was similar in the first and second time periods (83.9% v 79.1%). However, 31/51 (61%) retrieved children were intubated by referring hospital staff in 1993–94, compared to 227/269 (84%) in 2000–01. Referring hospital staff gained central venous access in 11% v 18% and arterial access in 22% v 19% of retrieved children in the first and second time periods respectively. This was in spite of a significant reduction in the proportion of children on whom these procedures were performed. Conclusion: Referring hospital staff are performing a greater proportion of initial airway and vascular access procedures undertaken in the stabilisation of sick children retrieved by a specialised paediatric retrieval team. The provision of this service has not resulted in the loss of vital skills at the local hospital.